Dobór zmiennych w modelach DEA do badań porównawczych produktywności na przykładzie krajowych spółek dystrybucji energii elektrycznej - Witkowska, Joanna (Selection of variables in DEA models for comparative studies of productivity on the example of Polish electrical energy distribution utilities, 2006)
The article presents variables selection issues for comparative studies on productivity of Polish electrical energy distribution utilities. There have been considered series of financial, technical and organizational variables describing utilities’ activity. Two essential phases of variables selection have been described, as well as substantial and statistical analysis. The selected series of variables seems to be adequate from the distribution utilities point of view, and also meet the demands of DEA (data envelopment analysis) method used for productivity measure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 424-434